+0  
 
+4
316
2
avatar+28 

Hi.

 

I recently stumbled upon this question and still can't figure out how to prove it. This is a GCSE question and it has never been this hard before.

 

\(k=2^p - 1\)

\(N = k^2 -1\)

Show that 2^(p+1) is a factor of N

Thanks in advance,

bqrs01

bqrs01  May 27, 2017
edited by bqrs01  May 28, 2017
 #1
avatar
+3

You say "Show that N is a factor of 2^(p+1)" ??. Are you sure it is not the reverse? That is:

Show that 2^(p+1) is a factor of N?

Guest May 27, 2017
 #2
avatar+92888 
+5

ok :)

 

\(k=2^p-1\\ N=k^2-1\\ N=(2^p-1)^2-1\\ N=2^{2p}-2*2^p+1-1\\ N=2^p*2^p-2*2^p\\ N=2^p(2^p-2)\\ N=2^{p+1}(2^{p-1}-1)\\ so\\ 2^{p+1}\text{ is a factor of }N\)

 

 

So I have shown that  2^(p+1) is a factor of N

Which is the other way around from what you asked.

Melody  May 28, 2017

5 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.